Reconfiguring urban metabolism through sustainable parametric landscape design development of urban fringe in San Matero, Rizal - Comboy, Marione Deanna T.; Villajuan, Jose Dan (Quezon City College of Architecture, University of the Philippines, Diliman, 2017)
The municipality of San Mateo, Rizal is deemed as one of the emerging urban fringe with diverse land use and spatial composition. The sprawl of Metro Manila cities' urbanity to San Mateo, Rizal has deliberately affected anthropological movements and ecological dynamics adversely. These issues deject ecosystem stability and quality of living which are prompted as vital considerations with increasing development of San Mateo, Rizal towards urbanity. The thesis proposes comprehensive and sustainable parametric design solutions applied on the urban fringe in mitigating the negative anthropogenic inflictions on ecosystems focusing on an array of landscape architectural facets : spatial efficiency, biodiversity, and its subsets on transportation, built environment and social environment. The design process includes integration of sustainable parametric design in green structure technology and master planning. This proposal advances the idea that in order to reconfigure San Mateo, Rizal's existing urban metabolism condition, parametric landscape architectural interventions are recommended to address problems concerning mechanisms on urban growth.
included appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines, Diliman